PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI YANG MENGALAMI DISMINOR PASCA MASSAGE EFFLEURAGE - Dwi Yulinda; Melisa Putri Rahmadhena (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Dysmenorrhea is pain during menstruations would be impaced in activities of adolescence. Management of dysmenorrhea can be reduce with non-pharmaco therapy include massage and compresses. Massage effleurage one of non-pharmaco therapy. Ruduction of dysmenorrhea can also affect the amount of reduced bleeding, thereby minimizing the risk of anemia during menstruastion. This study aimed to assess the effect of massage effleurage on adolescence to haemoglobin. Research was conducted on adolescence which is divided into two groups. They are the control group; and the treatment group which was given massage effleurage. Haemoglobin was measured after two cycle of menstruation. The analytical method used is Student T-test. Massage effleurage increased haemogobin which was significantly on the second cylce menstruation increase in the treatment group compared to the control group at p <0.05. Massage effleurage on adolescence with disminorrhea can be increase of haemoglobin level